"Slowed for several months": A mixed methods comparison of minor, moderate, and extreme speeders. (December 2021) - Peterson, Colleen M.; Gaugler, Joseph E.; Nelson, Toben F.; Pereira, Mark A.
Highlights: Mixed methods comparisons offer insight into speeding decision-making and beliefs. Minor, moderate, extreme speeders share some beliefs but still speed differently. All speeders report perceived mastery and discount speeding as a major threat. Minor speeders make more extensive, permanent changes after key events. Moderate and extreme speeders make more relative and temporary speed changes. Abstract: Speeding remains a major and consistent contributor to motor vehicle fatalities in the U.S. Using a parallel convergent mixed methods approach, we compared minor, moderate, and extreme U.S. speeder types (N = 293) to gain a better understanding of why U.S. drivers speed to the degree that they do. An online survey collected quantitative data on self-reported characteristics, speeding behaviors, and roadway behaviors after key events (collisions, speeding tickets) and given passenger presence. Analysis of qualitative data from participants explaining their roadway behaviors and beliefs identified several speeding-related themes. Themes shared to the same extent by all speeder types include not typically citing speeding a cause of a collision and good drivers not needing to change speeding behaviors (i.e., perceived mastery). However, the permanence and extent of speed reductions after key events and with passengers did vary by speeder type, with minor speeders making more extensive and permanent changes. Qualitative and quantitative data both underscore the perception that speeding is not a high priority threat to roadway safety.  Findings suggest continued research using conservative and nuanced definitions of speeding is warranted to understand how similar perceptions result in a spectrum of speeding behaviors.